Modifying monolayer behaviour by incorporating subphase additives and improving Langmuir–Blodgett thin film deposition on optical fibres - Partridge, Matthew; Wong, Rebecca; Collins, Mike; James, Stephen W.; Davis, Frank; Tatam, Ralph P.; Higson, Seamus P. J. (Elsevier, 2014)
Experiments showing the possibility of modifying the behaviour of calix[4]resorcinarene monolayers at the air–water interface and optimising the deposition of multilayer coatings onto optical fibres are presented. The nature of the subphase is fundamental to the behaviour of monolayers and their utility in coating and sensing applications. Here we show initial studies exploring the modification of the calix[4]resorcinarene monolayer–water interaction through the introduction of dipole altering alcohol additives to the aqueous subphase. We explored the effect of this modification for three small alcohols. The resulting isotherms of the materials showed a reduction in the surface pressure and area per molecule required in order for the monolayer to reach its point of collapse. Incorporation of alcohols shifted the point of collapse, leading to the application of ethanol being successful in improving the transfer of material via Langmuir–Blodgett coating onto optical fibres at lower pressures. This method may prove useful in allowing greater control over future sensor surface coatings.
Keywords: Monolayers; Multilayers; Coatings; Optical properties